Моделі організаційно - технологічних рішень з виконання будівельно -монтажних робіт - Горбач, М. В. (Ways to Improve Construction Efficiency, 2013)
The necessity of new approaches to strategy selection options of construction work to ensure that contractual terms of their performance and minimize wasted resources for their implementation, taking into account the nature of relationships between the work performed.